Teachers’ Perceived Ethical Roles in Educating Students with ASD: A phenomenological Study - Tawagen, Jane I; Pedro, Florenda L; Samson, Sheela G; Dulnuan, Joyce Ann C; Liswid, Sheryll S; Daganos, Juliane Louisse L; Agpay, Renila V; Ignacio, Teresita D (International Journal of Rehabilitation and Special Education (IJRSE), 2026)
Equitable, and quality education of all learners worldwide are the advocates of  United Nations Educational, Scientific, and Cultural Organization (UNESCO) together  with Sustainable Development Goal 4 (SGD 4). Nevertheless, this devotion presents  both ethical and practical challenges in the administration of inclusive practices,  specifically for teachers teaching learners with Autism Spectrum Disorder (ASD).  There is limited research on how Filipino teachers personally experience and make  ethical decisions in inclusive classrooms for learners with ASD, particularly using a  phenomenological approach in resource-limited and culturally specific contexts.  The primary aim of this study is to explore the lived experience of teachers in  the province of Benguet regarding their perceived ethical roles when educating  learners with mild to moderate ASD in the inclusive classroom settings. Data were  collected with an in-depth semi structured interview and analyzed through the  lens of Colaizzi’s (1978) method. The data gathered from the study revealed that  teachers demonstrated a deep commitment to their learners, as reflected in the  emerged themes, encapsulated in the acronym AGAPe. AGAPe stands for: Associated  Emotions within Ethical Dilemmas, Guideposts in Decision-making, Approaches  and Strategies in Navigating Ethical Dilemmas, and Personal Growth. Implications  suggest that respondents encountered ethical dilemmas arising from conflicts  between institutional policies, administrative directives, professional boundaries,  and personal values. Furthermore, emotional demands, limited training, and the  need to balance individual and collective welfare within the classroom are the factors  of ethical dilemma.
Keywords: ethical dilemma; inclusion; professional boundaries; empathy; professional growth